2012
DOI: 10.3766/jaaa.23.9.2
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Hearing Loss and Middle Ear Pathology in Young Infants Referred through a Newborn Universal Hearing Screening Program in Australia

Abstract: Conductive hearing loss was found to be a common diagnosis among infants referred through screening. ATSI infants had significantly higher rates of middle ear pathology and conductive hearing loss at birth and showed poor resolution of middle ear pathology over time compared to non-ATSI infants. Future research using a direct measure of middle ear function as an adjunct to the automated auditory brainstem response screening tool to distinguish conductive from sensorineural hearing loss may facilitate prioritiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 61 publications
(59 reference statements)
0
40
0
Order By: Relevance
“…However, successful recording of OAEs and AABR require both healthy inner ear and normal or near normal middle ear function. While passing AABR indicates global normal auditory function, AABR is not sensitive to subtle middle ear and cochlear conditions [14,15]. Hence a pass in AABR screening may not always assure normal middle ear function.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, successful recording of OAEs and AABR require both healthy inner ear and normal or near normal middle ear function. While passing AABR indicates global normal auditory function, AABR is not sensitive to subtle middle ear and cochlear conditions [14,15]. Hence a pass in AABR screening may not always assure normal middle ear function.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, Aithal et al [15] studied 211 infants (54 Aboriginal, 157 Caucasian) referred through a newborn hearing screening program in Queensland, Australia. They reported higher prevalence of middle ear pathology in Aboriginal infants (44.4%) compared to Caucasian infants (28.7%).…”
mentioning
confidence: 98%
“…A pass in AABR does not rule out subtle middle ear dysfunction [28,30]. Similarly, a pass in HFT or TEOAE test alone does not guarantee normal middle ear function, as infants and children with subtle middle ear dysfunction can pass this test [29,36].…”
Section: Limitationsmentioning
confidence: 99%
“…In fact, the ethnicity of subjects in the present study differs from earlier WBA test performance studies due to inclusion of Aboriginal infants in the study. Previous studies have shown that Australian Aboriginal infants have a higher prevalence of middle ear dysfunction (Aithal et al 2012;, 1996. Recently, Aithal et al (In press) found that Aboriginal neonates had lower WBA than their Caucasian counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…Note: * indicates significant difference at an alpha level of <.05 Table 5.4 illustrates the various WBA percentile values (0, 10, 50, 90 and 100) for both Aboriginal (n= 36 ears) and Caucasian (n= 172 ears) neonates with a pass in the HFT and DPOAE screening test battery. Normative range for WBA was determined as the region between 10 th and 90 th percentiles (Aithal et al, 2012). Frequency ( …”
Section: Wba In Aboriginal and Caucasian Neonates Who Passed The Hft mentioning
confidence: 99%